Recipe for Success: Suggestions and Recommendations for the Isolation and Characterisation of Bacteriocins. (17th June 2021) - Twomey, Ellen; Hill, Colin; Field, Des; Begley, Máire
Abstract : Bacteriocins are bacterially produced antimicrobial peptides. Although only two peptides have been approved for use as natural preservatives foods, current research is focusing on expanding their application as potential therapeutics against clinical pathogens. Our laboratory group has been working on bacteriocins for over 25 years, and during that time, we have isolated bacteriocin-producing microorganisms from a variety of sources including human skin, human faeces, and various foods. These bacteriocins were purified and characterised, and their potential applications were examined. We have also identified bioengineered derivatives of the prototype lantibiotic nisin which possess more desirable properties than the wild-type, such as enhanced antimicrobial activity. In the current communication, we discuss the main methods that were employed to identify such peptides. Furthermore, we provide a step-by-step guide to carrying out these methods that include accompanying diagrams. We hope that our recommendations and advice will be of use to others in their search for, and subsequent analysis of, novel bacteriocins, and derivatives thereof.